Thinking about good and evil Jewish views from antiquity to modernity - Allen, Wayne (The Jewish Publication Society, 2021)
"The most comprehensive book on the topic, Thinking about Good and Evil traces salient Jewish ideas about why innocent people seem to suffer, why evil individuals seem to prosper, and God's role in matters of (in)justice, from antiquity to modernity"--
Keywords: Bibel -- Altes Testament; Geschichte; Rabbinismus; Jüdische Theologie; Das Böse; Das Gute; Jüdische Philosophie; Yetzer hara (Judaism); Good and evil / Religious aspects / Judaism